Dementia Improvement after Plasma Exchange for Familial Hypercholesterolemia - Allen J. Orehek (Case Reports in Neurological Medicine)
Worldwide dementia related memory issues affect a great number of patients and families. In this case, a “senior moment” was noted at age fifty and issues with memory and mind progressed resulting in early retirement from work. The patient described here was given a diagnosis of “Pre-Alzheimer’s disease” and presented for further accurate evaluation, diagnosis, and management. The medical management resulted in an improvement in the patients memory and cognitive ability.